Factors related with osteoporosis treatment in postmenopausal women. Issue 28 (July 2018) - Rossi, Lia Mara Montagner; Copes, Rafaela Martinez; Dal Osto, Leo Canterle; Flores, Clovis; Comim, Fábio Vasconcellos; Premaor, Melissa Orlandin
Abstract : Abstract: Although fractures had high mortality and morbidity, many studies proved that fracture risk might be decreased by pharmacological therapy, although a low treatment adherence rate is observed. The aim of this study was to identify factors associated with osteoporosis treatment in postmenopausal women. A cross-sectional study was carried out from March to August 2013 at the primary care setting. Postmenopausal women were recruited. A standardized questionnaire was applied. Women who were using at least one of the following drugs at the moment of the survey were considered as current treatment: bisphosphonates, raloxifene, estrogen, calcitonin, teriparatide, or strontium ranelate. Women who had used any of the mentioned medications before the study were considered as past treatment. Of the 1025 women included in the study, 8% were on current treatment, 5.7% had past treatment, and 86.3% had not received treatment. Treated women (either current or past) had a higher rate of osteoarthritis, had more falls, had higher education level, presented a higher rate of private health insurance, and received more information about osteoporosis. They also had more dual-energy x-ray absorptiometry (DXA) scans and were more frequently diagnosed with osteoporosis by these DXA scans. The factors independently associated with treatment in the regression analysis were the DXA scan itself, the diagnosis of osteoporosis by DXA, and information about osteoporosis. Current and past treatments of osteoporosis were associated with DXA and information. These results suggest that some measures to inform women about osteoporosis and or even the popularization of DXA scans could improve the treatment.